Magnetic anisotropy in Fe phthalocyanine film deposited on Si(110) substrate: standing configuration - Bartolomé, Juan; Bartolomé, Fernando; García, Luis Miguel; Gredig, Thomas; Schuller, Ivan K.; Cezar, Julio C. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2017)
In this contribution we report on the structural and magnetic properties of an Fe phthalocyanine (FePc) thin film deposited on a silicon substrate. The planar FePc molecules order spontaneously in a standing configuration, i.e., with the molecular plane perpendicular to the substrate. The x-ray linear polarized absorption and x-ray magnetic circular dichroism experiments at the Fe-L2,3 edges at T = 6 K were performed, concluding that at this temperature the film displays magnetic anisotropy with the main easy axis perpendicular to the substrate. This result is explained in terms of the FePc single molecule anisotropy which has its larger moment in the molecule plane. Thus, the standing configuration in polycrystalline thin films favors statistically that, at the macroscopic array level, the magnetic easy anisotropy axis is normal to the substrate.